WRITTEN CORRECTIVE FEEDBACK IN EFL WRITING: GENDER-BASED PREFERENCES AND PERCEPTIONS OF UNIVERSITY STUDENTS - Hussein , Shoresh; Hasan, Idrees (Humanities Journal of University of Zakho, 2026)
Despite the extensive research on Written Corrective Feedback (WCF) among EFL students, limited attention has been given to how gender may shape learners’ perceptions and preferences regarding feedback in academic writing within the Kurdish context. The present study investigates the gender-based beliefs and preferences of Kurdish EFL university students toward WCF in academic writing. This study aims to fill this gap by examining how male and female students perceive various WCF approaches and how these perceptions influence their paragraph writing development. A quantitative approach was adapted for the study, which involved 60 second-year students from the English Department at the University of Zakho, College of Humanities, during the academic year 2024–2025. A 14-item Likert-scale questionnaire was used, and the data were analyzed using the Statistical Package of Social Science (SPSS) version 25, applying descriptive statistics, independent samples t-tests, and Cronbach’s Alpha to analyze the reliability of the questionnaire items. Findings indicated that both male and female students viewed WCF as helpful to enrich their motivation, awareness of error, and writing skills. However, statistical gender effects emerged in emotional responses and feedback preferences. Despite these affective and strategic differences, no systematic gender differences were observed in attitudes toward the overall utility of WCF. These findings suggest the advantages of a gender-sensitive feedback pedagogy that acknowledges students' affective and strategic natures to ensure more effective and comprehensive EFL writing instruction